2016
DOI: 10.15252/embj.201693927
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid leukemia with transdifferentiation plasticity developing from T‐cell progenitors

Abstract: Unfavorable patient survival coincides with lineage plasticity observed in human acute leukemias. These cases are assumed to arise from hematopoietic stem cells, which have stable multipotent differentiation potential. However, here we report that plasticity in leukemia can result from instable lineage identity states inherited from differentiating progenitor cells. Using mice with enhanced c-Myc expression, we show, at the single-cell level, that T-lymphoid progenitors retain broad malignant lineage potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 74 publications
(119 reference statements)
3
19
0
Order By: Relevance
“…This is especially true for the poor‐risk disease of mixed‐phenotype acute leukemia (MPAL) (Matutes et al , ), which for many years suggested that early hematopoietic progenitors can have the potential to undergo either myeloid or lymphoid differentiation. In accordance, there have been numerous reports suggesting the persistence of a myeloid potential in early B‐ and T‐lymphoid precursors (Wada et al , ), and the current study by Riemke et al () showed that the expression of MYC/BCL2 in T‐lymphoid progenitors resulted not only in pure T cell but also in mixed myeloid/T‐cell phenotypes. Interestingly, unique features including a gene expression pattern similar to dendritic cells (DC) characterize the T‐lymphoid progenitor‐derived myeloid leukemia, which is in line with earlier findings showing preserved DC developmental potential during T‐lymphoid differentiation (Manz et al , ).…”
Section: Refined Model Of Human Acute Myeloid Leukemia Originsupporting
confidence: 92%
See 2 more Smart Citations
“…This is especially true for the poor‐risk disease of mixed‐phenotype acute leukemia (MPAL) (Matutes et al , ), which for many years suggested that early hematopoietic progenitors can have the potential to undergo either myeloid or lymphoid differentiation. In accordance, there have been numerous reports suggesting the persistence of a myeloid potential in early B‐ and T‐lymphoid precursors (Wada et al , ), and the current study by Riemke et al () showed that the expression of MYC/BCL2 in T‐lymphoid progenitors resulted not only in pure T cell but also in mixed myeloid/T‐cell phenotypes. Interestingly, unique features including a gene expression pattern similar to dendritic cells (DC) characterize the T‐lymphoid progenitor‐derived myeloid leukemia, which is in line with earlier findings showing preserved DC developmental potential during T‐lymphoid differentiation (Manz et al , ).…”
Section: Refined Model Of Human Acute Myeloid Leukemia Originsupporting
confidence: 92%
“…In line, putatively activating NOTCH1 mutations are found in several AML cases and gene expression signatures allow the detection of a respective “T‐cell origin” cohort. In the present study, published gene expression data sets suggest approximately 5% of all human AML cases to be of potential T‐cell progenitor origin, that is, showing hints for a pathogenesis similar to the murine MYC/BCL2‐driven model (Riemke et al , ).…”
Section: Refined Model Of Human Acute Myeloid Leukemia Originsupporting
confidence: 62%
See 1 more Smart Citation
“…The manufacture, quality control, storage, release and delivery of ATMPs The design and execution of early phase clinical trials with ATMPs The interdisciplinary management of toxicities The active follow-up of patients treated with ATMPs, Interact on both national and EU level Should be accredited in terms of process and structure quality by the local competent authority as the basis for a national accreditation May apply for the coverage of costs based on their national accreditation at health insurance companies for certain products Should be obliged to establish and maintain a network of exchange with other accredited centers to avoid redundancy and excessive consumption of resources and the potential to differentiate [29] may add to the general risks of defined cell populations and challenges the benefit of meticulous characterization of cellular components. Thus, detailed definition of a cellular product and subsequent correlation with clinical outcome will be an important step to further clarify these issues.…”
Section: Mission Of Academic Competence Centers For Atmpsmentioning
confidence: 99%
“…In a recently published study, 5 we addressed the question of the leukemic lineage fate outcome of oncogene-transformed Tcell precursors. Using CD4/CD8 double-negative (DN2) T-cell progenitors expressing either Myc/Bcl2 (v-myc avian myelocytomatosis viral oncogene homolog / B-cell CLL/lymphoma 2) or MLL-AF9 (mixed lineage leukemia-ALL1 fused gene from chromosome 9) oncogenes, we showed at the single cell level that transformed DN2 cells resulted not only in pure T-lymphoid leukemia as assumed but also in mixed myeloid/T-cell leukemia.…”
mentioning
confidence: 99%